Food consumption and advanced β cell autoimmunity in young children with HLA-conferred susceptibility to type 1 diabetes: a nested case-control design - Virtanen, Suvi M; Nevalainen, Jaakko; Kronberg-Kippilä, Carina; Ahonen, Suvi; Tapanainen, Heli; Uusitalo, Liisa; Takkinen, Hanna-Mari; Niinistö, Sari; Ovaskainen, Marja-Leena; Kenward, Michael G; Veijola, Riitta; Ilonen, Jorma; et al. (The American journal of clinical nutrition, 2012)
Background: Evidence for the role of food consumption during childhood in the development of β cell autoimmunity is scarce and fragmentary. Objective: We set out to study the associations of longitudinal food consumption in children with the development of advanced β cell autoimmunity. Design: Children with advanced β cell autoimmunity (n = 232) (ie, with repeated positivity for antibodies against islet cells) together with positivity for at least one of the other 3 antibodies analyzed or clinical type 1 diabetes were identified from a prospective birth cohort of 6069 infants with HLA-DQB1–conferred susceptibility to type 1 diabetes who were born in 1996–2004, with the longest follow-up to the age of 11 y. Repeated 3-d food records were completed by the families and daycare personnel. Diabetes-associated autoantibodies and diets were measured at 3–12-mo intervals. Four control subjects, who were matched for birth date, sex, area, and genetic risk, were randomly selected for each case. Results: In the main food groups, only intakes of cow-milk products (OR: 1.05; 95% CI: 1.00, 1.10) and fruit and berry juices (OR: 1.09; 95% CI: 1.02, 1.12) were significantly, although marginally, associated with advanced β cell autoimmunity. The consumption of fresh milk products and cow milk–based infant formulas was related to the endpoint, whereas no evidence was shown for consumption of sour milk products and cheese. The intake of fat from all milk products and protein from fresh milk products was associated with risk of advanced β cell autoimmunity. Conclusion: Intakes of cow milk and fruit and berry juices could be related to the development of advanced β cell autoimmunity. This trial was registered at http://clinicaltrials.gov as number NCT00223613.